A 3D parallel boundary element method on unstructured triangular grids for fully nonlinear wave-body interactions. (1st January 2019) - Dombre, E.; Harris, J.C.; Benoit, M.; Violeau, D.; Peyrard, C.
Abstract: This paper presents the development and validation of a three-dimensional numerical wave tank devoted to studying wave-structure interaction problems. It is based on the fully nonlinear potential flow theory, here solved by a boundary element approach and using unstructured triangular meshes of the domain's boundaries. Time updating is based on a second-order explicit Taylor series expansion. The method is parallelized using the Message Passing Interface (MPI) in order to take advantage of multi-processor systems. For radiation problems, with cylindrical bodies moving in prescribed motion, the free-surface is updated with a fully Lagrangian scheme, and is able to reproduce reference results for nonlinear forces exerted on the moving body. For diffraction problems, semi-Lagrangian time-updating is used, and reproduces nonlinear effects for diffraction on monopiles. Finally, we study the nonlinear wave loads on a fixed semi-submersible structure, thereby illustrating the possibility to apply the proposed numerical model for the design of offshore structures and floaters. Highlights: Nonlinear potential flow model reproduces forces on moving surface-piercing bodies. Experimental data matches boundary element solution up to fourth-order harmonics. Parallelization of boundary element method efficient on moderate computing clusters. Model results match expectations for complex Dutch tri-floater platform design.